A step towards a better understanding of corrosion of zirconium in nitric acid with additions of fluorine: Focus on the role of the presence of an initial oxide film. (June 2022) - Gwinner, B.; Balbaud-Célérier, F.; Fauvet, P.; Gruet, N.; Laghoutaris, P.; Miserque, F.; Robin, R.
Abstract: The presence of fluorine is known to drastically reduce the corrosion resistance of zirconium in nitric acid. Nevertheless corrosion processes involved for this system appear controversial, especially concerning the role played by the initial oxide film (ZrO2 ) that can naturally be formed in nitric acid. To study the contribution of the initial oxide film, zirconium samples were pre-oxidized in several ways so as to obtain different thicknesses of the initial oxide film. Then, the corrosion evolution of these samples was studied in nitric acid with fluorine additions. It appears that the initial oxide film present on surface plays a protective role for corrosion. But as the oxide film slowly dissolves, this protective role may only be transitory (depending on the thickness of the initial oxide film). When the oxide film has been sufficiently dissolved, it breaks by a process of initiation, growth and coalescence of pits. Zirconium is then directly attacked by fluorine and its corrosion rate increases largely. After the complete vanishing of the initial oxide film, corrosion becomes uniform and the corrosion rate decreases slowly: the corrosion process is limited by the diffusion and the consumption of fluorine. Graphical Abstract: ga1 Highlights: The impact of the initial oxide film was investigated on the corrosion of zirconium in nitric acid with fluorine. Pre-oxidation of zirconium was performed in different ways to obtain various oxide films. The initial oxide film acts as a transient protective barrier. The mechanism of attack by fluorine of the zirconium oxide film is better understood.